A nonlinear analysis for GRS walls conceiving kinematics of failure against pullout - S. Patra; J. T. Shahu (Lowland Technology International, 2018)
A modified nonlinear analysis is presented to investigate the pullout response of geosynthetic reinforced soil (GRS) walls. The analysis conceives a hyperbolic stress-strain relationship for the backfill, the kinematics of the failure and the deformation compatibility between the soil and the reinforcement. The deformation compatibility is incorporated by introducing an updated discretization technique, and the true projected length of the reinforcement after deformation is evaluated by a simple computational scheme. A case study is presented for an instrumented full-scale reinforced soil wall to validate the present analysis. The maximum tension in the reinforcement at each level is computed considering the effect of compaction, and the results are compared with the measured values and those predicted by AASHTO simplified method. The comparison shows that the present analysis gives a better estimation of the reinforcement tension thus can be easily integrated with the existing method. A parametric study is also conducted mainly to determine the effect of stiffness and strength parameters of the subgrade which have a significant influence on the design of GRS walls against pullout failure for all practical applications.